فاعلية إستخدام خرائط المفاهيم على التحصيل المعرفى والإتجاهات لمقرر نظم ومشكلات التعليم لدى طالبات كلية التربية الرياضية جامعة بنى سويف" - ياسمين عيد (Beni-Suef University, Faculty of Physical Education, 2023)
يهدف البحث إلى التعرف على فاعلية إستخدام خرائط المفاهيم على التحصيل المعرفى والإتجاهات لمقرر نظم ومشكلات التعليم لدى طالبات كلية التربية الرياضية جامعة بنى سويف، وقد إستخدمت الباحثة المنهج التجريبى ، حيث إشتملت عينة البحث على (30) طالبة تم إختيارهم بالطريقة العمدية من طالبات شعبة التدريس الفرقة الرابعة بكلية التربية الرياضية ، وقد أسفرت النتائج إلى أن خرائط المفاهيم لها تآثير إيجابى على مستوى التحصيل المعرفى والإتجاهات لمقرر نظم ومشكلات التعليم لدى طالبات كلية التربية الرياضية جامعة بنى سويف.AbstractThe research aims to identify the effectiveness of using concept maps on the cognitive achievement and trends of the educational systems and problems course among the students of the Faculty of Physical Education, Beni Suef University. and the researcher used the Experimental approach.The research sample has been chosen by Intentional way and included (30) female students, and the results showed that concept maps have a positive effect on the level of cognitive achievement and trends for the course of education systems and problems among female students of the Faculty of Physical Education, Beni Suef University.